Perkembangan Sistem Pendidikan di Saudia Arabia - Husnul Khotimah; Mislaini Mislaini; Delita Marni (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Islamic Fofocation in Saudi Arabit. Mern efecation in Saudi Arabur has a centrot rule in shaping the identity and valurs of Saudi Arabian society. The entry hus long been a center of Islamic educational actrity, playing an important role in the spread and maintenance of Ishante teuchings throughout the world. This article discusses several key aspects of Islamic education in Saudi Arabia, including educational structure, curriculum. The structure of Jalomic education in Saudi Arabie consists of various levelt, from primary education to tertiary level. Blamic schouly tách religious koowintre, the Koran, hadith, and other religious studies The sammic exhocation curriculon is directed at ensuring a lerp understanding of Islamic teaching and justering slanec moral and ethnul values in everyday life Islamic education in S Saudi Arabia hat a is a significant impact on shaping in shaping the character and worldview of its people. Even though it continues to develop, challenges ant debates continue to emerge along with efforts in aljan Islamic education with the dermenuts of the mondern era. ThecomparisonbetweeneducationinSaudi Arabiaand education in Indonesia is that Saudi Arabia is an Islamic monarchy that uses Islam as the foundation of its education, while Indonesia is a democratic country that adheres to a more inclusive education system.